2022
DOI: 10.1038/s41598-022-15450-w
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age-specific serum creatinine can predict adverse pregnancy outcomes

Abstract: Serum creatinine level (SCr) typically decreases during pregnancy due to physiologic glomerular hyperfiltration. Therefore, the clinical practice of estimated glomerular filtration rate (eGFR) based on SCr concentrations might be inapplicable to pregnant women with kidney disease since it does not take into account of the pregnancy-related biological changes. We integrated the Wonju Severance Christian Hospital (WSCH)-based findings and prior knowledge from big data to reveal the relationship between the abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…CLSI recommends that utilizing two approaches to establish a 95% con dence interval (CI) for each subclass (e.g., age group and sex): either selecting quali ed reference individuals or including a su cient number of participants, with a recommended minimum of 120 subjects 7 . We previously analyzed the SCr concentrations in 4,004 pregnant women to predict adverse pregnancy outcomes 11 . We attempted to satisfy the rst recommendation of the CLSI by carefully selecting reference SCr measurements in healthy pregnant women without a medical diagnosis of a chronic disease or adverse pregnancy outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CLSI recommends that utilizing two approaches to establish a 95% con dence interval (CI) for each subclass (e.g., age group and sex): either selecting quali ed reference individuals or including a su cient number of participants, with a recommended minimum of 120 subjects 7 . We previously analyzed the SCr concentrations in 4,004 pregnant women to predict adverse pregnancy outcomes 11 . We attempted to satisfy the rst recommendation of the CLSI by carefully selecting reference SCr measurements in healthy pregnant women without a medical diagnosis of a chronic disease or adverse pregnancy outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Kang et al 11 demonstrated that the SCr concentration could predict the risk of adverse pregnancy outcomes and the number of co-occurring adverse pregnancy outcomes. When using the GW-speci c SCr distribution, the predictive power of adverse pregnancy outcomes was more robust based on beta coe cients and their p-values compared to the raw SCr distribution 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Harel et al 22 reported that blunted glomerular hyper ltration in early pregnancy may be associated with an increased risk of PTB and perinatal mortality. In our previous study 11 , we identi ed that SCr levels could predict the risk of adverse pregnancy outcomes and the number of co-occurring adverse pregnancy outcomes. When using the GWspeci c SCr distribution, the predictive power of adverse pregnancy outcomes was more robust based on the beta coe cients and their p-values compared with the raw SCr distribution 11 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously analyzed 10,126 SCr measurements from 4,004 pregnant women to predict the adverse pregnancy outcomes 11 . In this study, only 1,370 SCr measurements, which were obtained from 940 normal pregnant women with a healthy full-term baby, were extracted and analyzed.…”
Section: Analysis Of Raw Datamentioning
confidence: 99%
“…The analysis included women who had singleton or multiple births at > 38 weeks of gestation, were aged 16–50 years at the time of delivery, and had at least one SCr measurement during pregnancy. We previously analyzed the SCr concentrations in 4,004 pregnant women to predict adverse pregnancy outcomes 11 . EMR extracted data were reviewed by an expert from the Department of Medical Information, and LIS data were reviewed by laboratory medicine specialists.…”
Section: Methodsmentioning
confidence: 99%